Platform Strategiarchy as a Tool for Reducing Information Asymmetry, Taking into Account the Scale, Cardinality and Order of the Strategy - Vyshnevskyi, O. (Економічний вісник Донбасу, 2023)
The purpose of study is to substantiate the conceptual foundations of reducing information asymmetry using platform strategiarchy taking into account scale, cardinality and order of the strategy.
The scientific novelty obtained as a result of the research lies in the description of new scientific concepts: strategiarchy, platform strategiarchy, information asymmetry, scale of strategy, cardinality of strategy, order of strategy scale. The introduction of which allows us to form a scientific and theoretical basis for the further institutionalization of strategizing, which creates conditions for reducing information asymmetry in the process of developing the digital economy.
In a broad sense, strategiarchy is a model of social structure aimed at increasing subjectivity in society and minimizing information asymmetry through the institutionalization of strategizing.
Key characteristics of strategiarchy:
1. Every capable individual and legal entity has a public strategy.
2. Every capable individual and legal entity has the ability and opportunity to evaluate any strategy (of the other capable individual and legal entity).
In a narrow sense, strategiarchy is a system for coordinating strategies at various levels of governance and management. In other words, strategiarchy is the result of ascent from the abstract (general theory of strategizing) to the concrete (digital platform for strategy consolidation).
The implementation of strategiarchy using a digital platform is called platform strategiarchy. The introduction of the concepts “scale of strategy”, “cardinality of strategy”, “order of strategy scale” allows you to organize and compare strategies, including on the appropriate digital platform.
The scale of strategy is equal to the product of influence and resource of the subject of strategy implementation. The quantitative assessment of the "resource" is determined by the number of employees of the organization. "Impact" is quantified through the number of customers or stakeholders. The cardinality of a strategy is defined as the square root of the scale of the strategy. The order of strategy cardinality is determined by the order of the number characterizing the cardinality of the strategy, i.e. the decimal logarithm of the power. The calculation of these characteristics is demonstrated on specific examples (United Nations, USA, Facebook, Kiev, Ilon Musk, Felix Arvid Ulf Kjellberg, Robinson Crusoe).
As a result, placing strategies on digital platforms allows to reduce information asymmetry in various communications between companies, government and individuals. Метою дослідження є обґрунтування концептуальних основ зменшення інформаційної асиметрії за допомогою платформної стратегіархії з урахуванням масштабу, потужності та порядку стратегії.
Наукова новизна дослідження полягає в описі нових понять: стратегіархія, платформна стратегіархія, загальні характеристики стратегії (масштаб, потужність і порядок стратегії). Використання цих понять дозволяє сформувати теоретичну основу для подальшої інституціоналізації стратегування, яке створює умови для зменшення інформаційної асиметрії у умовах розвитку цифрової економіки.
У широкому сенсі стратегархія – це модель соціального устрою, спрямована на підвищення суб’єктності в суспільстві та мінімізацію інформаційної асиметрії через інституціоналізацію стратегування.
Основні характеристики стратегархії: (1) кожна дієздатна фізична та юридична особа має публічну стратегію; (2) кожна дієздатна фізична та юридична особа має здатність і можливість оцінити будь-яку стратегію (іншої дієздатної фізичної або юридичної особа).
У вузькому розумінні стратегархії – це система координації стратегій на різних рівнях управління. Одночасно, стратегархії являє собою результат сходження від абстрактного (загальна теорія стратегування) до конкретного (цифрова платформа для консолідації стратегій).
Імплементація стратегіархії на цифровій блокчейн платформі називається платформною стратегіархією. Введення понять масштаб, потужність та порядок стратегії дозволяє упорядкувати та співставляти стратегії в тому числі на відповідній цифровій платформі.
Масштаб стратегії дорівнює добутку впливу та ресурсу суб’єкту реалізації стратегії. Кількісна оцінка «ресурсу» визначається через чисельність працівників організації. Кількісна оцінка «впливу» визначається через кількість клієнтів або зацікавлених сторін. Потужність стратегії визначається як квадратний корінь масштабу стратегії. Порядок потужності стратегії визначається порядком числа, що характеризує потужність стратегії тобто десятковий логарифм потужності. На конкретних прикладах (ООН, США, Facebook, місто Київ, Ілон Маск, Фелікс Арвід Ульф Чельберг, Робінзон Крузо) продемонстровано розрахунок цих характеристик.
У підсумку розміщення стратегій на цифрових платформах дозволяє знизити асиметрію інформації при різними комунікації між компаніями, урядом та індивідами.